The complete mitochondrial genome of Phrynocephalus guinanensis (Reptilia, Squamata, Agamidae). (3rd March 2016) - Fu, Caiyun; Chen, Wei; Jin, Yuanting
Abstract: Recent phylogenetic researches discovered no reciprocal monophyly between morphological species of Phrynocephalus putjatia and P. guinanensis, P. guinanensis exhibits extensive sexual color dimorphism, whereas P. putjatia does not have. The complete mitochondrial genome of the putative taxa, Phrynocephalus guinanensis, was determined in order to compare the mitogenomes of both ecological forms. The mitogenome sequence was 16, 279 bp in size. It consists of 13 protein-coding, 22 tRNA, 2 rRNA genes and 3 control region, and its gene order and gene content were identical with the mitogenome of P. putjatia .